Preschool Children Feeding Patterns And Early Childhood Oral Health Impact In Tanah Merah, Kelantan, Malaysia - Nizamuddin Pardan; Ruhaya Hasan; Norsamsu Arni Samsudin; Wan Muhamad Amir W Ahmad (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: Poor feeding patterns increase risk of Early Childhood Caries (ECC), which can cause negative impacts on oral health-related quality of life (OHQoL) of preschool children and parents. This study aims to assess feeding patterns of preschool children and OHQoL of the children and their parents in Tanah Merah. Methods: A cross-sectional study was conducted involving 134 preschool children aged 5-6 years old from eight private preschools, chosen by multi-staged stratified cluster sampling. Parents answered adopted self-administered questionnaire on feeding patterns and oral health-related impacts. Mann-Whitney U test and Kruskal-Wallis test were used to compare the median between groups of feeding patterns. Results: A total of 122 parents responded. Majority of the children had history of bottle-feeding (97.5%) and being given solid food during infancy (61.2%). Many children were still using bottle to drink (38.5%). Majority were still given formula milk at least three times daily (51.1%) and were feed with bottle to put to sleep (97.9%). The Child Impact Section (CIS), Family Impact Section (FIS) and Overall ECOHIS mean scores were 2.39 (SD=3.41), 0.71 (SD=1.45) and 3.10 (SD=4.41), respectively. Most common impact reported in CIS was ‘oral pain’ (26.2%) whereas in FIS, ‘parents felt guilty’ (7.4%). None of feeding patterns were found significantly different in terms of ECOHIS score median (p-value>0.05). Children OHQoL reporting by proxy should be treated as complementary. Conclusion: Many preschool children were involved in prolonged, frequent and nocturnal bottle-feeding. No significant difference in median ECOHIS scores found according to feeding patterns. REFERENCE 1. Nembhwani HV, Winnier J. Prevalence of Early Childhood Caries and Associated Risk Factors in Navi Mumbai, Maharashtra: A Cross-sectional Descriptive Study. J Oral Heal Community Dent. 2022;16:14–18. doi:10.5005/jp-journals-10062-0124 2. Salleh NC, Yaw SL, Muttalib KBA, Rahman JA. National oral health survey of preschool children 2015 (NOHPS 2015), Vol. I: oral health status and caries treatment needs of 5-year-old children. Oral Health Division, Ministry of Health Malaysia. 2017. (Cited 2022 September 30). Available from: https://drive.google.com/file/d/1E-BkRmeiNSzI2dLLPoUX7NQqRrdknwqs/view 3. Pitts NB, Baez RJ, Diaz-Guillory C, et al. Early Childhood Caries: IAPD Bangkok Declaration. Pediatr Dent. 2019;41:176–178. doi: 10.1111/ipd.12490 4. Pereira JT, Knorst JK, Luz PB, Bonfadini I, Scapinello M, Hugo FN, et al. Impact of early childhood caries and maternal behaviors on oral health-related quality of life of children. Pesqui Bras Odontopediatria Clin Integr. 2020;20:1–13. doi: 10.1590/pboci.2020.065 5. Dolah S, Eusufzai SZ, Alam MK, Wan Ahmad WMA. Factors influencing oral health-related quality of life among preschool children in district of Kota Bharu, Malaysia: A cross-sectional study. Pesqui Bras Odontopediatria Clin Integr. 2020;20:1–10. doi:10.1590/pboci.2020.008 6. Chaffee BW, Feldens CA, Rodrigues PH, Vítolo MR. Feeding practices in infancy associated with caries incidence in early childhood. Community Dent Oral Epidemiol. 2015;43:338–348. doi: 10.1111/CDOE.12158 7. Feldens CA, Rodrigues PH, de Anastácio G, Vítolo MR, Chaffee BW. Feeding frequency in infancy and dental caries in childhood: a prospective cohort study. Int Dent J. 2018;68:113–121. doi: 10.1111/idj.12333 8. Feldens CA, Giugliani ERJ, Vigo Á, Vítolo MR. Early feeding practices and severe early childhood caries in four-year-old children from southern Brazil: A birth cohort study. Caries Res. 2010;44:445–452. doi: 10.1159/000319898 9. Anil S, Anand PS. Early childhood caries: Prevalence, risk factors, and prevention. Front Pediatr. 2017;5:157. doi: 10.3389/fped.2017.00157 10. Institute for Public Health (IPH), National Institutes of Health Ministry of Health Malaysia. National Health and Morbidity Survey (NHMS) 2016: Maternal and Child Health. Vol. II: Findings, 2016. Institute for Public Health (IPH), National Institutes of Health Ministry of Health Malaysia. 2016. (Cited 2022 September 30). Available from: https://iku.moh.gov.my/images/IKU/Document/REPORT/2016/NHMS2016ReportVolumeII-MaternalChildHealthFindingsv2.pdf 11. Buhari N, Zainal Abidin F, Mani S, Khan I. Oral Hygiene Practices and Bottle Feeding Pattern Among Children with Early Childhood Caries: A Preliminary Study. Ann Dent. 2016;23:1–8. doi: 10.22452/adum.vol23no2.1 12. Tinanoff N, Baez RJ, Diaz Guillory C, Donly KJ, Feldens CA, McGrath C et al. Early childhood caries epidemiology, aetiology, risk assessment, societal burden, management, education, and policy: Global perspective. Int J Paediatr Dent. 2019;29:238–248. doi: 10.1111/ipd.12484 13. Watt R, Sheiham A. Inequalities in oral health: A review of the evidence and recommendations for action. Br Dent J. 1999;187:6–12. doi: 10.1038/sj.bdj.4800191a 14. Hashim AN, Yusof ZYM, Esa R. The Malay version of the Early Childhood Oral Health Impact Scale (Malay-ECOHIS) - assessing validity and reliability. Health Qual Life Outcomes. 2015;13:1–10. doi: 10.1186/s12955-015-0386-2 15. Pahel BT, Rozier RG, Slade GD. Parental perceptions of children’s oral health: The Early Childhood Oral Health Impact Scale (ECOHIS). Health Qual Life Outcomes. 2007;5:1–10. doi: 10.1186/1477-7525-5-6 16. Kebebe T, Assaye H. Intention, magnitude and factors associated with bottle feeding among mothers of 0–23 months old children in Holeta town, Central Ethiopia: a cross sectional study. BMC Nutr. 2017;3:53. doi: 10.1186/s40795-017-0174-y 17. American Academy of Pediatric Dentistry. Policy on early childhood caries (ECC): Classifications, consequences, and preventive strategies. Ref Man Pediatr Dent. 2020;79–81 18. World Health Organization. Infant and young child feeding. https://www.who.int/news-room/fact-sheets/detail/infant-and-young-child-feeding. 2021. Accessed 13 Dec 2021 19. White JM, Bégin F, Kumapley R, Murray C, Krasevec J. Complementary feeding practices: Current global and regional estimates. Matern Child Nutr. 2017;13(S2):e12505. doi:10.1111/mcn.12505 20. Wang L, Van Grieken A, Van Der Velde LA, Vlasblom E, Beltman M, L’Hoir MP et al. Factors associated with early introduction of complementary feeding and consumption of non-recommended foods among Dutch infants: The BeeBOFT study. BMC Public Health. 2019; 19:388. doi:10.1186/s12889-019-6722-4 21. Martin CR, Ling PR, Blackburn GL. Review of infant feeding: Key features of breast milk and infant formula. Nutrients. 2016;8(279). doi:10.3390/nu8050279 22. Bakri NN, Rashid INA, Rahman FFA, Rasdi Z, Bohari NFM, Radzi NAM, et al. Determination of sugar types and content in formulated milk of infants and children in Malaysia. Malaysian J Fundam Appl Sci. 2019;15:695–698. doi: https://doi.org/10.11113/mjfas.v15n5.1495 23. Bridge G, Lomazzi M, Bedi R. A cross-country exploratory study to investigate the labelling, energy, carbohydrate and sugar content of formula milk products marketed for infants. Br Dent J. 2020; 228(3):198–212 24. Heyman M, Abrams S, AAP Section on Gastroenterology, Hepatology, and Nutrition, AAP Committee on Nutrition. Fruit juice in infants, children, and adolescents: current recommendations. Pediatrics. 2017;139(6):e20170967. doi:10.1542/peds.2017-0967 25. Rusali R, Najwa Hamali N, Muhammad Razi F, Mustafa N, Asilah Harun N, Azwani Mohd Shukri N. Early Childhood Feeding Practices and Its Association with Early Childhood Caries. J Food Nutr Res. 2019;7(11):801–804. doi: 10.12691/jfnr-7-11-7 26. Prakash P, Subramaniam P, Durgesh BH, Konde S. Prevalence of early childhood caries and associated risk factors in preschool children of urban Bangalore, India: A cross-sectional study. Eur J Dent. 2012;6:141–152. doi: 10.1055/s-0039-1698943 27. Mansoori S, Mehta A, Ansari MI. Factors associated with Oral Health Related Quality of Life of children with severe -Early Childhood Caries. J Oral Biol Craniofacial Res. 2019;9:222–225. doi: 10.1016/J.JOBCR.2019.05.005 28. Divaris K, Lee JY, Baker AD, Vann WF. Caregivers’ oral health literacy and their young children’s oral health-related quality-of-life. Acta Odontol Scand. 2012;70:390–397. doi: 10.3109/00016357.2011.629627